Conventional and modern therapeutic approaches in topical medication of onicosis - Lacramioara Ochiuz; Eliza Gratiela Popa; Cristina Mihaela Ghiciuc; Alexandra Bujor; Sha at Mousa; Carmen Gafitanu (Amaltea Medical Publishing House, 2021)
Onychosis therapy is an ongoing challenge considering the diversity of nail pathology and the barrier function of the nail plate. Among the nail diseases, we identify the primary onychodystrophies, caused by tics or mental disorders, as well as severe onychoses, caused by bacterial and/or fungal infections, manifested by the degradation of the matrix and the nail bed. Onychosis treatment is complex, lasting 6-8 months, and is often frustrating for both patients and healthcare professionals. In this article we have described a series of common onychoses from the etiopathological point of view, briefly presenting the general therapeutic approach. We also highlighted the classic and modern pharmaceutical formulations used in local nail medication. From the perspective of recent approaches, there is the development of therapeutic systems for transungual administration that ensure the prolonged and controlled drug release to optimize the pharmacotechnical performance of medication used in local therapy of onychosis.